Does religion cause violence?: multidisciplinary perspectives on violence and religion in the modern world - Cowdell, Scott; Fleming, Chris; Hodge, Joel; Osborn, Carly (Violence, desire, and the sacred, 2017)
Notes on Contributors ; Introduction -- Part 1. Does Religion Cause Violence? Chapter 1. Girard and the Myth of Religious Violence / William T. Cavanaugh ; Chapter 2. The Complex Relationship between Violence and Religion: A Response to William T. Cavanaugh's "Girard and the Myth of Religious Violence" / Petra Steinmair-Pösel ; Chapter 3. Why is God Part of Human Violence? The Idolatrous Nature of Modern Religious Extremism / Joel Hodge ; Chapter 4. Love Your Enemies: God's New World Order / Anthony J. Kelly -- Part 2. Violence and Deterrence in the Modern World. Chapter 5. "The War to End All Wars": Mimetic Theory and "Mounting to the Extremes" in a Time of Disaster / Sandor Goodhart ; Chapter 6. The Sacred is Back--But as Simulacrum / Jean-Pierre Dupuy ; Chapter 7. Forms of the Sacred and the Texture of Hope / Sarah Bachelard ; Chapter 8. The End of Politics? / Chris Fleming ; Chapter 9. Rites of Expulsion: Violence against Heretics in Early Modern Catholic France / Carly Osborn -- Part 3. Islamic Terrorism: A Case Study of Contemporary "Religious Violence". Chapter 10. Islam and Violence: Debunking the Myths / Asma Afsaruddin ; Chapter 11. Violence, Religion, and the Sacred: In Dialogue with Asma Afsaruddin's "Islam and Violence: Debunking the Myths" / Paul Dumouchel ; Chapter 12. Religion, Radicalization, and Violent Extremism? / Julian Droogan and Lise Waldek ; Chapter 13. Religious Extremism, Terrorism, and Islam: A Mimetic Perspective / Wolfgang Palaver ; Chapter 14. The Jihadist Current and the West: Politics, Theology, and the Clash of Conceptuality / Jonathan Cole -- Appendix: René Girard at a Glance / Scott Cowdell, Chris Fleming and Joel Hodge -- Glossary of Key Girardian Terms / Scott Cowdell, Chris Fleming and Joel Hodge -- Further Reading -- Index.